2018
DOI: 10.4081/dr.2018.7916
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy is a new diagnostic tool in diagnosis of common hypopigmented macular disease: A descriptive study

Abstract: One of the most frequent complaints in dermatology clinics is the eruption of hypopigmented patchy skin lesions. The aim of the study was to investigate the utility of dermoscopy in common hypopigmented macular diseases. Patients with the followings diseases were examined by dermoscopy: vitiligo, pityriasis alba, nevus depigmentosus, achromic pityriasis versicolor, idiopathic guttate hypomelanosis, and extragenital guttate lichen sclerosus. This study showed that these hypopigmented macular diseases might disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 23 publications
6
38
0
Order By: Relevance
“…On evaluating the dermoscopic features in our study with other authors, we found that perifollicular pigmentation was present in stable and repigmenting diseases in greater numbers when compared to unstable cases which was similar to the findings of Purnima et al and Wali et al 4,20 Jha et al and Al-Refu also found perifollicular pigmentation in 22.2% and 75% of patients respectively. 21,22 Similarly, perilesional/marginal hyperpigmentation in this study was 76.5% in stable and 36.4% in unstable cases which was concordant with the findings of Purnima et al (100% and 12%) but much more than Wali et al (23% and 0%), while Jha et al and Al-Refu had seen perilesional/marginal hyperpigmentation in 22% and 75% of cases. 4,[20][21][22] Also, intra/perilesional erythema with telangiectasia though not observed by many authors it was the most common finding in my study with 88.2% in stable disease and 84.8% in unstable disease.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On evaluating the dermoscopic features in our study with other authors, we found that perifollicular pigmentation was present in stable and repigmenting diseases in greater numbers when compared to unstable cases which was similar to the findings of Purnima et al and Wali et al 4,20 Jha et al and Al-Refu also found perifollicular pigmentation in 22.2% and 75% of patients respectively. 21,22 Similarly, perilesional/marginal hyperpigmentation in this study was 76.5% in stable and 36.4% in unstable cases which was concordant with the findings of Purnima et al (100% and 12%) but much more than Wali et al (23% and 0%), while Jha et al and Al-Refu had seen perilesional/marginal hyperpigmentation in 22% and 75% of cases. 4,[20][21][22] Also, intra/perilesional erythema with telangiectasia though not observed by many authors it was the most common finding in my study with 88.2% in stable disease and 84.8% in unstable disease.…”
Section: Discussionsupporting
confidence: 91%
“…21,22 Similarly, perilesional/marginal hyperpigmentation in this study was 76.5% in stable and 36.4% in unstable cases which was concordant with the findings of Purnima et al (100% and 12%) but much more than Wali et al (23% and 0%), while Jha et al and Al-Refu had seen perilesional/marginal hyperpigmentation in 22% and 75% of cases. 4,[20][21][22] Also, intra/perilesional erythema with telangiectasia though not observed by many authors it was the most common finding in my study with 88.2% in stable disease and 84.8% in unstable disease. Intra/perilesional erythema with telangiectasia was also seen by Jha et al in 37% cases and Al-Refu K in 8% cases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Whether the depigmentation of a spot is complete or incomplete has been evaluated by dermoscopy in recent years, and this has contributed to the diagnosis of vitiligo [9]. However, dermoscopy is associated with a disadvantage in that it is based on local observation within very narrow range.…”
Section: Discussionmentioning
confidence: 99%